Gaps in Housing Assistance for Destitute Households in Poland: Conclusions of the National Studies - Rataj, Zuzanna (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
The system of social housing welfare in Poland is addressed to poor and very poor households. It does not apply to the group of underprivileged households who earn their income that on the one hand disqualifies them from applying for council flat but on the other hand is not sufficient to apply for a mortgage loan to purchase of a flat on commercial market. The response to the needs of such households were the flats available via Social Housing Associations (TBS). The research conducted in 2015–2016 showed the gaps in the system of social housing welfare in Poland. The income criteria that allow for renting particular types of flats – either council flats or TBS flats – are defined in a way that creates an income gap between them. As a consequence, households whose income levels fall into that gap have no possibility to avail of any welfare to satisfy their housing needs. The only possibility for them is to rent an apartment available on the market – with higher rents and often informal type of lease. Moreover, the income criteria that authorize for the rental of a TBS flat are on the same level as those authorizing for a mortgage loan. In this context, can they still be considered a form of housing support? Are the housing welfare solutions available for underprivileged households effective? Do they fulfil their goal? Those questions are addressed by the author in this article alongside other related issues. The research has been conducted within the project entitled “Social housing and its role in fulfilling the housing needs of underprivileged households in Poland” financed by the National Science Centre (2014/13/N/HS4/02100).